HEAVY METAL IONS REMOVAL USING MAGNETIC BIO-SORBENT BASED ON AGRO-LIGNOCELLULOSIC MATERIALS - DANESHFOZOUN, SAFOURA (2017)
Heavy metals are highly toxic and non-biodegradable which effective strategies must be developed for bioremediation or their removal from the environment. Biosorption is an eco-friendly, economical and easy technique to be implemented in removal of heavy metals.